Numerical Simulation of Metasurface Grating to Function as Polarization Modulator in Quantum Key Distribution Systems - Ali Qader Baki*,; Shelan Khasro Tawfeeq, (Iraqi Journal of Laser, 2023)
Polarization modulation plays an important role in polarization encoding in quantum key distribution. By using polarization modulation, quantum key distribution systems become more compact and more vulnerable as one laser source is used instead of using multiple laser sources that may cause side-channel attacks. Metasurfaces with their exceptional optical properties have led to the development of versatile ultrathin optical devices. They are made up of planar arrays of resonant or nearly resonant subwavelength pieces and provide complete control over reflected and transmitted electromagnetic waves opening several possibilities for the development of innovative optical components. In this work, the Si nanowire metasurface grating polarizer is designed by COMSOL Multiphysics Software to operate in the visible region and transmit the transverse magnetic polarization of light. The same structure can be rotated by different angles, i.e., 90o, 45o, and -45o to mimic the function of polarization modulation in quantum key distribution systems. The designed structure has an extinction ratio of ~ 60000 and a wide angular tolerance range of (-20o - 20o).